Guide to the Caribbean Basin Initiative (U.S. Department of Commerce WashingtonUS, 1994)
Looks at the Caribbean Basisn Initiative as well as other preferential trade opportunities. Presents country profiles and key contacts. Oulines U.S. government programs for business development. Looks at customs procedures and documentation, U.S. regulatory requirements and safeguards.
Located in the Office of the Secretary General